(untitled) (Jurnal Manajemen dan Organisasi, 2026)
This study aims to analyze the influence of price perception and digital marketing on purchase decisions, mediated by consumer trust, in the context of competency-based training products at Sinergi Solusi Academy, Bogor. The research employed a quantitative approach using a survey method with questionnaires distributed to participants who had attended training and obtained BNSP professional certification. A total of 102 valid responses were collected using a non-probability sampling method. Data were analyzed using descriptive statistics and Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that price perception and digital marketing have a positive and significant effect on consumer trust and purchase decisions. Consumer trust also has a significant mediating role between price perception and digital marketing on purchase decisions. The dominant indicators influencing purchasing decisions are price affordability, digital accessibility, integrity, and payment method. These findings provide managerial implications for training institutions in formulating effective marketing strategies to increase consumer confidence and purchase decisions.